2016
DOI: 10.1016/j.jiph.2015.06.008
|View full text |Cite|
|
Sign up to set email alerts
|

Medical students’ awareness of and compliance with the hepatitis B vaccine in a tertiary care academic hospital: An epidemiological study

Abstract: Medical students had a low level of compliance with the HBV vaccination program, regardless of their knowledge and awareness of the disease and vaccination. We recommend that programs and campaigns be developed to increase the overall awareness of this disease. We also suggest that a mandatory HBV vaccination program should be implemented to improve the compliance rate among medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 16 publications
2
27
0
2
Order By: Relevance
“…This study found that 65.7% of the students were not aware about their HBV immune status and only half of them (51.7%) had received HBV vaccine with almost third of them receiving complete vaccination of three doses (Figure 1). Almost similar percentage of vaccinated students who had received the vaccination was reported in previous local studies conducted in King Khaled University hospital (Ghomraoui et al, 2016), and in Aljouf University (Al-Hazmi, 2015). While, a higher percentage of vaccinated students (88.9%) was reported among dental students in Hail region of Saudi Arabia (Haridi et al, 2016), which was explained by receiving of adequate training courses and the availability of mandatory free of charge vaccination to all health care workers.…”
Section: Students' Compliance With Hbvsupporting
confidence: 81%
See 1 more Smart Citation
“…This study found that 65.7% of the students were not aware about their HBV immune status and only half of them (51.7%) had received HBV vaccine with almost third of them receiving complete vaccination of three doses (Figure 1). Almost similar percentage of vaccinated students who had received the vaccination was reported in previous local studies conducted in King Khaled University hospital (Ghomraoui et al, 2016), and in Aljouf University (Al-Hazmi, 2015). While, a higher percentage of vaccinated students (88.9%) was reported among dental students in Hail region of Saudi Arabia (Haridi et al, 2016), which was explained by receiving of adequate training courses and the availability of mandatory free of charge vaccination to all health care workers.…”
Section: Students' Compliance With Hbvsupporting
confidence: 81%
“…In a similar study that was conducted on medical clinical trainee students from eleven universities in Europe and UK, 34% of them had been exposed to one of blood or body fluids hazards (Salzer et al, 2011). A higher incidents was reported among Lima, Peru medical students, as 46.7% of them suffered at least one incident during their clinical training (Ghomraoui et al, 2016).…”
Section: Potential Risk To Obhs Amongmentioning
confidence: 94%
“…Despite this recommendation, vaccination against HBV among HCSs in various African countries continues to fall below the target [15][16][17][18]. Some reasons for low vaccination coverage include transitory staff [19], busy schedule [20], lack of money to pay for the vaccine [21] and forgetfulness [22]. This is complicated by shortage of skilled HCWs, especially in low income countries, which may compel students to carry out procedures on their own especially in emergency situations [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have already revealed a lower knowledge on hepatitis B in general population, medical stu-dents, and patients (8)(9)(10)(11). One study from China also investigated Chinese physicians' awareness regarding the 2010 guidelines on the treatment of CHB.…”
Section: Discussionmentioning
confidence: 99%